Modulation of genomic and epigenetic end-points by celecoxib - Izzotti, Alberto (Oncotarget, 2018)
Celecoxib, a nonsteroidal anti-inflammatory drug that selectively targets cyclooxygenase-2, is a promising cancer chemopreventive agent. However, safety concerns have been raised in clinical trials evaluating its ability to prevent colorectal adenomas. The rationale for the herein reported studies was to analyze genomic and epigenetic end-points aimed at investigating both the chemopreventive properties of celecoxib towards cigarette smoke-associated molecular alterations and its possible adverse effects. We carried out three consecutive studies in mice treated with either smoke and/or celecoxib. Study 1 investigated early DNA alterations (DNA adducts, oxidative DNA damage, and systemic genotoxic damage) and epigenetic alterations (expression of 1,135 microRNAs) in lung and blood of Swiss H mice; Study 2 evaluated the formation of DNA adducts in lung, liver, and heart; and Study 3 evaluated the expression of microRNAs in 10 organs and 3 body fluids of ICR (CD-1) mice. Surprisingly, the oral administration of celecoxib to smoke-free mice resulted in the formation of DNA adducts in both lung and heart and in dysregulation of microRNAs in mouse organs and body fluids. On the other hand, celecoxib attenuated smoke-related DNA damage and dysregulation of microRNA expression. In conclusion, celecoxib showed pleiotropic properties and multiple mechanisms by counteracting the molecular damage produced by smoke in a variety of organs and body fluids. However, administration of celecoxib to non-smoking mice resulted in evident molecular alterations, also including DNA and RNA alterations in the heart, which may bear relevance in the pathogenesis of the cardiovascular adverse effects of this drug.